Compact V-Shaped MIMO Antenna For LTE And 5G Communications - Mohammed Ibrahim, Ayman; Mohd Ibrahim, Imran; Shairi, Noor Azwan (Wydawnictwo SIGMA-NOT, 2020)
A new small V-shaped MIMO antenna with dimensions of the antenna 21 × 24 × 0.8 mm within the bands of (4.4-4.9) and (5.15-5.925) GHz was designed, and the fabrication and measurement outcomes derived from the use of the MIMO prototype revealed that the fractal MIMO antenna. The small and simple fractal antenna demonstrated high isolation of less than -18.5 dB and envelope correlation coefficient less than 0.05. These attributes are suitable for mobile, which is being introduced into Japanese markets.